SUB-CONVENTIONAL CONFLICT AND DETERRENCE STABILITY IN SOUTHERN ASIA: BETWEEN THE BOMB AND THE BRINK - Rai, Shubham (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Focusing on India-Pakistan’s conflict relations, this paper explores the intricate interaction of sub-conventional conflict, nuclear deterrence, and strategic stability in Southern Asia. Nuclearisation of Southern Asia has created a stability-instability paradox in which reciprocal nuclear deterrence lowers the likelihood of all-out conventional conflict even as low-intensity conflicts and crises continue to exist. In this paper, examine the development of Indo-Pakistani conflicts—from full-scale battles in the pre-nuclear era to proxy conflicts and terrorist incursions under the nuclear shadow and evaluate how nuclear capabilities have changed strategic behaviour. The paper creates a theoretical framework to examine how nuclear deterrence at the strategic level coexists with continuous sub-conventional conflicts by drawing on academic literature and current occurrences. The results show that whereas nuclear weapons have created a kind of strategic stability by preventing large-scale conflict, they have also promoted proxy conflicts and constrained military operations, endangering regional peace. We contend that whether crises escalate or stay contained is shaped by credible deterrence, doctrinal postures, and confidence-building initiatives acting together. Enduring security in Southern Asia, the paper argues, will rely on managing sub-conventional threats, establishing nuclear red lines, and implementing bilateral risk-reduction initiatives to avoid miscalculations in this unstable nuclear context.